Comparison of success of tracheal intubation using Macintosh laryngoscope-assisted Bonfils fiberscope and Truview video laryngoscope in simulated difficult airway - Bangaru Vivek; R Sripriya; Gayatri Mishra; M Ravishankar; S Parthasarathy (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Restriction of head and neck movements prevents the alignment of the oral, pharyngeal, and laryngeal axes and increases the incidence of difficult tracheal intubation in patients with cervical spine fractures. Video laryngoscopes have gained an important role in the management of difficult intubation, especially in situations with limited head and neck movements. This study compares the success of intubation using Macintosh laryngoscope assisted Bonfils® fiberscope (ML-BF) with TruviewPCD video laryngoscope (TV) in patients with simulated restricted head and neck movements. Material and Methods: One hundred and fifty-two patients satisfying the inclusion criteria were randomly allocated to two groups of 76 each. Patients were made to lie supine on the table without a pillow and a soft collar was used to restrict head and neck movements. After a standardized premedication-induction sequence, tracheal intubation was done either with ML-BF or TV. Success of intubation, time taken for successful intubation, hemodynamic changes, airway trauma, and postoperative oropharyngeal morbidity were noted. Results: Intubation was successful in all the 76 patients in direct laryngoscopy-Bonfils fiberscope group and 75 out of 76 patients in TV group within the specified time (90 s). The median time taken for successful intubation with TV and ML-BF were 44 (range 26-80) s and 49 (range 28-83) s, respectively. Hemodynamic changes, airway trauma, and postoperative oropharyngeal morbidity were similar in both groups. Conclusion: Both TV and ML-BF are equally effective for successful tracheal intubation in patients with simulated restricted head and neck movements. In cases of difficult laryngeal visualization with routine Macintosh laryngoscope, Bonfils can be used as an adjunct to achieve successful intubation in the same laryngoscopy attempt.